2016
DOI: 10.18520/cs/v110/i2/234-240
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of <I>Elaeocarpus blascoi</I> Weibel, an Endemic and Endangered Tree Species of Palni Hills, Western Ghats, India

Abstract: effects of Batawali (Tinospora tuberculata) on germination and seedling growth of plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Physical and mechanical dormancy is the most common inhibitor of germination in many species. Threatened tree species such as Cupressus atlantica (Youssef et al 2012), Elaeocarpus blascoi Weibel (Ramasubbu and Irudhyaraj 2016) and Intsia bijuga (Colebr.) Kuntze (Thaman et al 2006) exhibit exogenous dormancy where the hard seed coats inhibit water penetration that is required for embryo growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical and mechanical dormancy is the most common inhibitor of germination in many species. Threatened tree species such as Cupressus atlantica (Youssef et al 2012), Elaeocarpus blascoi Weibel (Ramasubbu and Irudhyaraj 2016) and Intsia bijuga (Colebr.) Kuntze (Thaman et al 2006) exhibit exogenous dormancy where the hard seed coats inhibit water penetration that is required for embryo growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds germinate in April with the onset of rain so moisture may be a requirement for germination. The inherent stony endocarp in many members of the genus seems to be a plausible factor for poor germination (Bhuyan et al 2002;Khan et al 2003;Ramasubbu and Irudhyaraj 2016). Some studies have revealed low (1-3%) and erratic seed germination in Elaeocarpus ganitrus Roxb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these have been reported in a few publications, details are incomplete or seem to have been omitted (Stewart & Balcar 2003, 2008Ramasubbu & Irudhayaraj 2016). Two publications claim rediscovery of the species (Vijayan et al 2011;Irudhayaraj & Ramasubbu 2014), indeed, of the exact same tree, though our efforts have previously been published (Stewart & Balcar 2003, 2008.…”
Section: Records Of Thementioning
confidence: 95%
“…Moreover, the phylogenetic relationship between Elaeocarpus species are poorly understood, and only a few molecular studies have been undertaken so far, with the number of loci and taxon sample being limited (Prasannan et al, 2020). In addition, some of the taxonomic studies carried out in the past (Irudhayaraj & Ramasubbu, 2014; Irudhyaraj & Ramasubbu, 2017; Meijer, 1995; Murti, 1993; Ramamoorthy, 1976; Ramasubbu & Irudhyaraj, 2016; Saldanha, 1984; Vijayan, 2017) had also assisted in the identification of the genus in the Indian subcontinent. However, problems of nomenclature, typification, species delimitation, and species identification, with many of these issues have been arising from the citation of incorrectly identified materials.…”
Section: Introductionmentioning
confidence: 99%